Analysis of Qur'an Tahfidz House (RTQ) Management at Rumah Tahfidz Center Lampung - Susanti, Ressi; Rohman, Miftahur; Hayati, Rina Mida (Jurnal Ilmiah Iqra', 2024)
Analysis of Qur'an Tahfidz House (RTQ) Management at Rumah Tahfidz Center Lampung. Qur'an Tahfidz House (RTQ) is one of the non-formal Islamic educational institutions that continues to maintain its existence amidst the hegemony of formal educational institutions. In its development, RTQ can be an alternative non-formal education that students can pursue to support their formal education. Using qualitative research methods, data was collected through observation and in-depth interviews; this research aims to discover management strategies at RTQ Al-Qur'any and RTQ Nurul Jannah. The research results found that: (1) curriculum management was carried out through planning, implementation, and evaluation by RTQ administrators and caregivers; (2) student management is carried out by mapping student needs, recruiting all registrants, grouping them into three levels, as well as student evaluations conducted by halaqah administrators; (3) Management of educators and educational personnel is carried out by analyzing needs, recruitment, cadre formation, as well as the development of the Asatidz council and administrative staff.